Advertisement Remove all ads

Advertisement Remove all ads

Advertisement Remove all ads

The first three terms of an AP respectively are 3y – 1, 3y + 5 and 5y + 1. Then y equals:

(A) –3

(B) 4

(C) 5

(D) 2

Advertisement Remove all ads

#### Solution

The first three terms of an AP are 3y – 1, 3y + 5 and 5y + 1 respectively

We need to find the value of y.

We know that if a, b and c are in AP, then:

b − a = c − b ⇒ 2b = a + c

∴2(3y+5) = 3y − 1 + 5y + 1

⇒6y + 10 = 8y

⇒10 = 8y −6y

⇒2y = 10

⇒y = 5

**Hence, the correct option is C.**

Concept: Arithmetic Progression

Is there an error in this question or solution?